A longitudinal study of the emerging self from 9 months to the age of 4 years - Kristen-Antonow, Susanne; Sodian, Beate; Perst, Hannah; Licata, Maria (Frontiers in Psychology, 2015)
The aim of this study was to investigate if children’s early responsiveness toward social partners is developmentally related to their growing concept of self, as reflected in their mirror self-recognition (MSR) and delayed self-recognition (DSR). Thus, a longitudinal study assessed infants’ responsiveness (e.g., smiling, gaze) toward social partners during the still-face (SF) task and a social imitation game and related it to their emerging MSR and DSR. Thereby, children were tested at regular time points from 9 months to 4 years of age. Results revealed significant predictive relations between children’s responsiveness toward a social partner in the SF task at 9 months and their MSR at 24 months. Further, interindividual differences in children’s awareness of and responsiveness toward being imitated in a social imitation game at 12 months proved to be the strongest predictor of children’s DSR at 4 years, while some additional variance was explained by MSR at 24 months and verbal intelligence. Overall, findings suggest a developmental link between children’s early awareness of and responsiveness toward the social world and their later ability to form a concept of self.